DIAGNOSTIC ACCURACY OF UTERINE ARTERY DOPPLER ULTRASOUND TO PREDICT PREECLAMPSIA IN PRIMIPAROUS FEMALES - Tayyaba Khan (Army Medical College Rawalpindi, 2019)
Objective: To determine the diagnostic accuracy of Doppler ultrasonography during second trimester of pregnancy, to predict pre-eclampsia (PE) in primigravidas.